(untitled) (Environment & Health, 2023)
Materials and methods. The following methods were used in the work: bibliographic; questionnaire method; statistical - for further application of correlation analysis (Spearman’s rank correlation method); mathematical methods - for quantitative assessment of indicators of self-assessment of the state of health and ecological and valeological awareness of young people. A survey of medical students was conducted in the cities of Kyiv and Lutsk. The sample of the study is 276 participants aged from 16 to 21 years old. The questionnaire of the World Health Organization (WHO) was adapted for the survey, the structure of which includes the following main characteristics: physical condition; limitation of activity due to physical condition; feeling pain; emotional condition; limitation of activity due to emotional state; difficulties in active communication caused by physical and emotional state; maintaining a healthy lifestyle. The basic data of the participants are age and gender. Results. The results of the questionnaire were converted into rank variables for further application of correlation analysis. As a result of the correlation analysis, it was found that: there is a significant relationship between the physical and emotional states of the interviewees (p